CMOS-Compatible Key Engineering Devices for High-Speed Silicon-Based Optical Interconnections - Wang, Jing (Springer Theses, Recognizing Outstanding Ph.D. Research, 2019)
This book discusses some research results for CMOS-compatible silicon-based optical devices and interconnections. With accurate simulation and experimental demonstration, it provides insights on silicon-based modulation, advanced multiplexing, polarization and efficient coupling controlling technologies, which are widely used in silicon photonics. Researchers, scientists, engineers and especially students in the field of silicon photonics can benefit from the book. This book provides valuable knowledge, useful methods and practical design that can be considered in emerging silicon-based optical interconnections and communications. And it also give some guidance to student how to organize and complete an good dissertation.